Design of an analog monolithic pixel sensor prototype in TPSCo 65 nm CMOS imaging technology. (1st January 2023) - Deng, W.; Aglieri Rinella, G.; Aresti, M.; Baudot, J.; Benotto, F.; Beole, S.; Bialas, W.; Borghello, G.; Bugiel, S.; Campbell, M.; Carnesecchi, F.; Charbon, E.; et al.
Abstract: A series of monolithic active pixel sensor prototypes (APTS chips) were manufactured in the TPSCo 65 nm CMOS imaging process in the framework of the CERN-EP R&D on monolithic sensors and the ALICE ITS3 upgrade project. Each APTS chip contains a 4 × 4 pixel matrix with fast analog outputs buffered to individual pads. To explore the process and sensor characteristics, various pixel pitches (10 µm–25 µm), geometries and reverse biasing schemes were included. Prototypes are fully functional with detailed sensor characterization ongoing. The design will be presented with some experimental results also correlating to some transistor measurements.